Canva sebagai alat pembelajaran digital untuk meningkatkan tulisan deskriptif siswa - Aulia Maharani; Fitri Handayani; Riyen Permata (Universitas Mahaputra Muhammad Yamin, 2026)
This study addresses a research gap in comparative investigations of visual media for teaching descriptive writing at the junior high school level. While previous studies have largely examined Canva in isolation and focused on higher education, limited attention has been given to its effectiveness compared to other visual platforms and across specific writing components. This quasi-experimental study examines the effects of Canva and Pinterest on seventh-grade students’ descriptive writing performance. Forty-four students were selected through purposive sampling and assigned to experimental and control groups. Data were collected through pre- and post-tests assessed by three independent raters using an analytical writing rubric. The findings reveal that students taught using Canva achieved significantly greater improvement than those taught using Pinterest, with a very strong effect size. Canva was particularly effective in supporting idea development and text organization, resulting in higher-quality written products. These results suggest that Canva is a pedagogically effective visual medium for teaching descriptive writing, and its integration through structured writing activities is recommended to enhance students’ writing skills.